Agresi intraspesifik dan waktu penemuan makanan pada semut invasif Anoplolepis gracilipes di Kebun Raya Bogor - Rion Apriyadi; Idham Sakti Harahap; Akhmad Rizali; Damayanti Buchori (Jurnal Entomologi Indonesia, 2016)
We studied the distribution of the Yellow Crazy Ant (Anoplolepis gracilipes) Smith (Hymenoptera: Formicidae) in Bogor Botanical Garden (BBG). Biological invasions by A. gracilipes can negatively impact other species. Individual nests of this ant can form supercolonies within which aggression is absent, intraspecific aggression occurs between workers from different supercolonies. The aim of this research was to study aggression between and resource discovery of different A. gracilipes supercolonies in BBG. Intraspecific aggression was calculated as three different aggression indices obtained by performing intercolonial arena encounters. Resource discovery was measured as time until honey baits in known distances to colony entrances were discovered. In 2013, we encountered five spatially distinct nest clusters of A. gracilipes in BBG, which cover ca. 25% of its area. Aggression tests showed that workers from KRB 1 were significantly more aggressive towards each other. The absence of intercolonial aggression between three of five nest clusters suggested that they actually belong to the same supercolony. On average, A. gracilipes needed less than 1 hour to find the food on bait plate in 20 m distance. We found 3 supercolonies of A. gracilipes which derived from 5 spatially distinct cluster of nests in BBG.